Hemorrhagic Transformation After Ischemic Stroke: Mechanisms and Management - Hong, Ji Man; Kim, Da Sol; Kim, Min (Frontiers in Neurology, 2021)
Symptomatic hemorrhagic transformation (HT) is one of the complications most likely to lead to death in patients with acute ischemic stroke. HT after acute ischemic stroke is diagnosed when certain areas of cerebral infarction appear as cerebral hemorrhage on radiological images. Its mechanisms are usually explained by disruption of the blood-brain barrier and reperfusion injury that causes leakage of peripheral blood cells. In ischemic infarction, HT may be a natural progression of acute ischemic stroke and can be facilitated or enhanced by reperfusion therapy. Therefore, to balance risks and benefits, HT occurrence in acute stroke settings is an important factor to be considered by physicians to determine whether recanalization therapy should be performed. This review aims to illustrate the pathophysiological mechanisms of HT, outline most HT-related factors after reperfusion therapy, and describe the prevention strategies for occurrence and enlargement of HT, including blood pressure control. Finally, we propose a promising therapeutic approach based on biological researches that would help clinicians treat such catastrophic complications.